Penapisan Jamur Antagonis Ganoderma sp. dari Tanaman Palmae di Kabupaten Kubu Raya Kalimantan Barat - Supriyanto, Supriyanto; Sulistyowati, Henny; Arifin, Nur (Perkebunan dan Lahan Tropika, 2026)
Screening of Ganoderma Antagonistic Fungi from Palmae Roots in Kubu Raya Regency, West Kalimantan, Indonesia. Basal stem rot (BSR) disease, caused by the pathogen Ganoderma sp., is the most important disease in palms (Arecaceae, formerly known as Palmae). To date, there is no effective method for controlling Ganoderma. In oil palms, several methods developed can only slow the rate of infection or extend the plant's productive period. Biological control is an alternative method for controlling Ganoderma and is currently under development. However, the development of biological control is hampered by its limited distribution. The most feasible approach is to identify effective indigenous antagonists from the rhizosphere of palms and develop methods for their utilization. This is because the palm family is a group of plants with high species diversity, so it is suspected that they also have a high diversity of rhizosphere fungi. Therefore, it is suspected that there are fungi antagonistic to Ganoderma that can be used as biological control agents against Ganoderma sp. This effort can be done by isolating and screening microorganisms from the rhizosphere of palm plants for their ability to act as antagonists against Ganoderma, and testing their activity in the rhizosphere of palm plants under various combinations of environmental factors thought to support their effectiveness in controlling Ganoderma. Specifically, this research aims to identify Ganoderma antagonists from the rhizosphere of palm plants in West Kalimantan that are effective in controlling BPB disease. The research has been conducted by isolating and testing the ability of fungi from the roots of palm plants in West Kalimantan in controlling Ganoderma sp. The results showed that 50.97% of fungi isolated from palm roots inhibited Ganoderma growth in vitro, with inhibition ranging from 70% to 83%. Given this ability, further testing is needed to determine the effectiveness of these fungi in controlling stem rot disease caused by Ganoderma in palm plants.